(untitled) (The Pakistan Development Review, 2025)
Financial markets (bond and stock markets), in conjunction with financial intermediaries (banks, insurance companies, pension funds) perform the important task of channelling surplus loanable funds from households, businesses, government and foreigners to households, businesses and governments in an efficient manner. This transfer of funds proceeds through a ‘direct’ and an ‘indirect’ channel, depicted in the diagram. A brief description of the structure of the financial market their main function and working is presented in the following table.